Pengaruh Kecerdasan Keuangan, Literasi Keuangan, Inovasi Bisnis dan Manajemen Resiko Terhadap Kinerja Keuangan UMKM Surabaya - Sevira Pahlevi Santoso; Hwihanus Hwihanus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The research analyzes to understand the influence of financial intelligence, financial literacy, business innovation and risk management on the financial performance of MSMEs in Surabaya. MSMEs are an important sector in the Indonesian economy, but many MSME actors still experience resistance, especially in terms of financial management. Data was collected through questionnaires from 60 respondents who are MSME actors in Surabaya, using a quantitative approach. The research results show that the majority of MSME players have limited understanding of financial management, including financial recording and reporting. Even though financial literacy and financial intelligence are recognized as important, the results of statistical analysis show that these two variables do not have a significant influence on the financial performance of MSMEs partially. However, training and education related to financial literacy is still needed because it has great potential to increase the financial resilience of MSMEs in the long term. This research also highlights that business innovation and the application of risk management can help MSMEs face market dynamics and economic challenges. Overall, this research provides an illustration that MSMEs need additional support, both through training and the use of technology, to be able to increase their competitiveness and business desires.